RECYCLING TECHNOLOGY INTO INDUSTRIAL TURNOVER OF BISMUTH AND MOLYBDENUM FROM DEAD CATALYST - O. S. Komarov; V. I. Volosatikov; D. O. Komarov; I. V. Provorova; T. D. Komarova (Литьë и металлургия)
The technology of separate extraction of bismuth and molybdenum from spent catalyst was presented and information on the effectiveness of its use in a composition of comprehensive modifier in the iron-carbon alloy was given.